Tinjauan Etika Bisnis Islam Terhadap Bisnis Salon Muslimah Zhafira Samarinda - Norvadewi Norvadewi (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2014)
The development of Islamic businesses has significantly increased recently. One of them is the beauty salon of Muslimah Zhafira. This objective of this study is to describe what concept the business of the beauty salon of Muslimah Zhafira is and how the ethical values of Islamic business implemented. This is a qualitative research which was conducted in natural setting through observation and interview. The findings show that the management staff and the owner of it understand how a business is not only about getting money, but it is also to get the blessings from Allah SWT. It is done by implementing the Islamic principles, that is, a business should be not only money-oriented benefits, but it should be also non-material benefits, development, continuity, and blessings. The implications of the Islamic ethical business is the implementation of transparency in the accounting and financial reports as stated in Islam to work professionally. The production management uses halal material, safe place, and standardized process, so that this system could be applied efficiently to give a wealthy to the owners and to those who involve in this business. Human resources management of beauty salon of muslimah Zhafira make the staffs enjoy and feel fair in terms of the salary system. This condition fits to the Islamic value, that is, Islam orders good cooperation to reach a win-win benefit. The marketing management of beauty salon of muslimah Zhafira applies family-based system by trying hard to fulfill the customers’ need. It also applies spiritual marketing strategy by implementing the Islamic akhlak.